An Orbital Localization Criterion Based on the Topological Analysis of the Electron Localization Function - Oña, Ofelia Beatriz (2013)
This work proposes a new molecular orbital localization procedure. The approach is based on the decomposition of the overlap matrix in accordance with the partitioning of the three-dimensional physical space into basins with clear chemical meaning arising from the topological analysis of the electron localization function. The procedure is computationally inexpensive, provides a straightforward interpretation of the resulting orbitals in terms of their localization indices and basin occupancies, and preserves the sigma/pi-separability in planar N-electron systems. The localization algorithm is tested on selected molecular systems.